A Case of Xanthogranulomatous Pyelonephritis - Shemrine Mark; Michael Brian Lim; Jiya Mulayamkuzhiyil; Justeena Joseph; Papiya Begum; Richard Schoor (Annals of Internal Medicine: Clinical Cases)
Xanthogranulomatous pyelonephritis (XGP) is a rare chronic destructive renal disease. This case describes a patient with a history of poorly controlled type 2 diabetes mellitus, hypertension, and nephrolithiasis who presented with nonspecific symptoms of left abdominal pain, fever, nausea, and vomiting. A Computed tomography scan showed left XGP that was surgically resected. Xanthogranulomatous pyelonephritis has similar features to malignancy. Hence, it is important to identify and treat this disease given that its aggressive nature can result in multiorgan spread and dysfunction. Xanthogranulomatous pyelonephritis has an excellent prognosis if managed appropriately.